Upaya Meningkatkan Hasil Belajar Peserta Didik Melalui Media Interaktif Berbasis Wordwall pada Pelajaran IPAS Kelas V SDN 30 Ampenan Tahun Ajaran 2024/2025 - Maharani, Agustina; Andriyatno; Fitriani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve students’ learning outcomes in the subject of Integrated Science and Social Studies (IPAS) for Grade V students at SD Negeri 30 Ampenan through the use of interactive media based on Wordwall. The research method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, which includes the stages of planning, action implementation, observation, and reflection. The research subjects were 28 fifth-grade students with diverse academic abilities. The study was conducted over three sessions using the Problem-Based Learning model supported by Wordwall media. The results showed an improvement in students’ learning outcomes from the pre-cycle stage, with an average score of 75 (46% mastery), to 78 in Cycle I (71% mastery), and further to 80 in Cycle II (89% mastery). Wordwall media proved effective in encouraging active student participation, increasing learning motivation, and facilitating conceptual understanding through interactive activities. Therefore, this approach can be used as an alternative strategy to enhance the quality of classroom learning, particularly in the IPAS subject.